An Analysis of Trends, Challenges, and Future Directions in Human Resources for the Tourism Sector: Rebuilding Bali's Workforce - Victor Bangun Mulia; I Wayan Suardana; I Nyoman Sukma Arida (Faculty of Economics and Business, University of Mataram, 2024)
Bali is renowned as a premier tourist destination, yet it faces significant challenges in terms of human resources within the tourism sector. This study aimed to analyze the current state of tourism human resources in Bali by examining their strengths, weaknesses, opportunities, and threats. Employing qualitative research methods, the study included thematic analysis based on insights from eight HR professionals in hotels and travel agencies across the island. The findings revealed that tourism HR in Bali possess adequate knowledge, skills, and a positive attitude toward their work. However, challenges persist, including a lack of mental readiness among younger professionals, limited English proficiency, uneven quality among tourism human resources, and insufficient supporting facilities for development. Addressing these issues is crucial for enhancing the overall quality of service and competitiveness in Bali's tourism sector, ensuring that it continues to thrive in an increasingly global market. This study highlights the need for targeted interventions to improve human resource capabilities and align them with the evolving demands of the industry.